1995
DOI: 10.1111/j.2042-7158.1995.tb05799.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Resiniferatoxin-stimulated, Calcium Inhibited but Phosphatidylserine-dependent Kinase, which is Distinct from Protein Kinase C Isotypes α, β1γ, δ, ε and η

Abstract: We have separated a resiniferatoxin-stimulated histone-kinase activity from human neutrophils, elicited mouse macrophages and murine alveolar macrophages by hydroxyapatite chromatography. The assay conditions for resiniferatoxin kinase were optimized as part of this study and in the presence of phosphatidylserine but absence of Ca2+ the Ka for histone IIIs phosphorylation by resiniferatoxin was calculated as 16 nM. Using a phosphate gradient of 20-500 mM, peaks of protein kinase C activity could be washed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…The binding sites for the alkyl moiety of CPS and the diterpene core of RTX are not well characterized. Furthermore, it has recently been shown that RTX, but not CPS, binds a kinase distinct from the PKC isotypes α, β, γ, δ and ε [57]. This result is in agreement with our finding that RTX did not activate AP-1.…”
Section: Discussionsupporting
confidence: 94%
“…The binding sites for the alkyl moiety of CPS and the diterpene core of RTX are not well characterized. Furthermore, it has recently been shown that RTX, but not CPS, binds a kinase distinct from the PKC isotypes α, β, γ, δ and ε [57]. This result is in agreement with our finding that RTX did not activate AP-1.…”
Section: Discussionsupporting
confidence: 94%